Process development of the straight grate process for iron ore pelletization at LKAB - Eriksson, Daniel (Chalmers tekniska högskola / Institutionen för energi och miljö, 2017)
This thesis describes the development of a simulation model replicating a straight grate induration furnace. The project has been performed in close collaboration with the iron ore pellets producing company LKAB. The model is applied to enable evaluation of process optimization measures and to improve energy efficiency of the straight grate process, more specifically LKAB’s MK3 unit located in Malmberget, Sweden. The project can be divided into three major sections; implementation of a reference case, study of the impact of a possible leakage and the examination of improved heat recovery within the process from outlet pellets. Initially, a reference case is set-up with typical input parameters for the MK3 process. Validation of the results were primarily done with a comparison with measured and simulated outlet gas temperature. Additional tools of validation consist of a mass balance, heat balance and fuel calculations. Two leakage cases were implemented to study the impact of a possible leakage and to evaluate the possibility for process optimization regarding unintended gas flows within the process. Furthermore, six cases were implemented to investigate the possibility for improved heat recovery from the outlet pellets and thereby increasing the energy efficiency of the process. The cases all included extensions of the cooling and drying sections, where the heat of the outlet pellets was recirculated to heat and dry the inlet pellets. For the reference case, without consideration taken to leakages occurring within the process, the model prediction overestimates the gas temperature with up to 111%. The large deviation is primarily due to leakages occurring in the process, mainly in the interface between heating and cooling. With the implementation of the leakage cases, the temperature deviation is overall lowered considerably, which indicates on possibilities for process improvements. For the study of improved heat recovery within the process, the results indicated a reduction in fuel consumption, ranging from ...